Design of Public Service Products of Sports Art Fitness under the Psychological Characteristics of Different Ages - Zhou Yue, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Objective: Different age stages will have different emphases in the selection of sports art fitness public service products. Therefore, this paper studies the design of sports art fitness public service products in light of the psychological characteristics of different ages. Methods: 150 middle-aged women with line dancing were selected as the research object, and 150 ordinary people who did not participate in physical exercise were used as the control group to design sports art fitness public service products according to the age of the exercisers. Results: The average score of spa (Social physical anxiety) is the highest for women under 30 years old, followed by women between 31-44 years old, and the lowest for women over 45 years old. Women with medium amount of exercise correspond to the highest spa, and women with large amount of exercise correspond to the lowest spa. The women who keep fit for half a year have the highest spa, followed by those who keep fit for 1-3 years, and finally those who keep fit for more than 3 years; Conclusion: This paper analyzes the psychological characteristics of different age stages and the factors affecting each stage, with a view to improve the utilization of sports art and fitness public service products